The Use of Trellis and Mulch Increased Fruit Production of Spaghetti Squash (Cucurbita pepo L.) - Kartika, Juang Gema; Karyana, Shinta Wulandari (Journal of Tropical Crop Science, 2017)
Spaghetti squash is squash of American origin that has spaghetti-like characteristic of fruit flesh, unlike any other squash varieties. This study aims to investigate the use of trellis and mulch to increase the spaghetti squash production. The experiment was conducted at the Experimental Station of Centre of Tropical Horticulture, Bogor from April to November 2016. The experiment used a completely randomized block design with four replicates. Two factors were tested, i.e. the use of trellis and mulch as the main plots, and accessions of the spaghetti squash as a sub-plot. The treatments were the use of trellis and mulch, mulch without the trellis, the trellis without mulch, and without the trellis and mulch. The spaghetti squash accessions used in this experiment were accessions from Taiwan (F1) and from America. Each experimental unit consists of five plants with a total a total of 160 plants. The results of this experiment showed that the growing squash using mulch and trellis had the greatest number of fruits per plant, more marketable fruits and had the largest fruit weight as compared with the other treatments. Taiwan accession had more fruits per plant and total marketable fruits, the largest fruit weight, the longest and widest fruits with large fruit diameter. Taiwan accession produced fruits at lower nodes of the plants, and fruits can be harvested earlier than the American accession. Correlation analysis indicated that the more fruits per plant, the more number of fruits that are marketable, the greater fruit weight and more fruits can be harvested from the higher nodes of the plants. From agronomical point of view, Taiwan spaghetti squash would be preferable to obtain the high fruit production provided the crops were mulched and grown with trellis.Keywords: Cucurbitacea, trellis, mulch, plant culture